Menganalisis Dampak Krisis Ekonomi Terhadap Tingkat Ekonomi Makro - Javier Syarif Ananta Syahbana; Yuyun Setyawati; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This Research Aims To Analyze The Impact Of The Economic Crisis On The Macroeconomic Level, Focusing On Key Variables Such As Economic Growth, Unemployment Rate, Inflation And Trade Balance. Using Historical Data And Quantitative Economic Analysis Methods, This Study Identifies Patterns And Trends That Emerge During Periods Of Economic Crisis In Various Countries. The Research Results Show That Economic Crises Tend To Cause A Significant Contraction In Gross Domestic Product (GDP), A Sharp Increase In The Unemployment Rate, As Well As Significant Price Fluctuations That Impact The Inflation Rate. In Addition, This Analysis Also Highlights How Fiscal And Monetary Policy Responses Can Speed Up Or Slow Down Economic Recovery. The Conclusions Of This Research Emphasize The Importance Of Appropriate Policy Strategies In Dealing With The Economic Crisis To Minimize Its Negative Impact On The Macro Economy.